The rhetoric of multi-display learning spaces: exploratory experiences in visual art discipines - Bligh, Brett; Lorenz, Katharina (Lillehammer University College, 2010)
Brett Bligh and Katharina Lorenz of The University of Nottingham, present the Multi-Display Learning Spaces (MD-LS) in this article. It comprises technologies to allow the viewing of multiple simultaneous visual materials, modes of learning which encourage critical reflection upon these materials, and spatial configurations which afford interaction between learners and the materials in orchestrated ways. They argue that Multi-Display Learning Spaces support complex, disciplinary reasoning within learning.